A research on the use of business intelligence for academic research. Issue 3 (4th July 2018) - Dadkhah, Mehdi; Lagzian, Mohammad
Abstract : Purpose: At the moment, business intelligence (BI) is known as the way for analyzing data in an organization. Simple search in the literature shows that there are many papers which discuss about BI applications and related matters. In addition, there are different approaches and tools that support using BI in organizations. This paper aims to focus on the use of BI tools for academic applications, and it describes how the academic area will benefit from using BI. Design/methodology/approach: This paper is based on using BI tools and other library studies. Findings: A process for using BI tools in academic applications has been presented. Also, two cases are stated about activities of e-learning participants and literature analysis, for which BI tools are used to analyze data and simplify difficult tasks. Originality/value: This paper shows how BI tools can be used for research and academic applications.